02 Utilization of Films In The Foreign Language Classrooms - Sonila PIRI; Jonida PETRO (Association of Social and Educational Innovation, 2016)
Throughout the recent decades of foreign language teaching the best new technology has been adapted and has been put in the context of teaching and learning. In particular the use of filmed materials has entered widely the process of foreign language didactics. Many are the reasons why language teachers should use their filmed material. They complement textbooks with authentic paralinguistic as well as extra linguistic cultural material featuring a reality as close to the place of language in the object of study. The utilization of these materials has raised curiosity and motivation in language learning. Even scientific research support this typology of learning. Of course the teacher must be careful in the selection of films which should include some specific criteria. The collection of the teaching materials related to the film selected parts, takes time and special specifications, but it provides in depth acquisition through the active participation of pupils.